1977
DOI: 10.1007/bf01768478
|View full text |Cite
|
Sign up to set email alerts
|

Une note sur la propriété de préfixe

Abstract: We give a necessary and sufficient condition for a language with the prefix property of R.V. Book to be regular.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

1978
1978
2017
2017

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
1
0
2
Order By: Relevance
“…Book formulated the "prefix property" in order to allow languages to "approximate" infinite sequences, and showed that for certain classes of languages, if a language in the class has the prefix property, then it is regular. A follow-up by Latteux [14] gives a necessary and sufficient condition for a prefix language to be regular. Languages whose complement is a prefix language, called "coprefix languages", have also been studied; see Berstel [4] for a survey of results on infinite words whose coprefix language is context-free.…”
Section: Related Workmentioning
confidence: 99%
“…Book formulated the "prefix property" in order to allow languages to "approximate" infinite sequences, and showed that for certain classes of languages, if a language in the class has the prefix property, then it is regular. A follow-up by Latteux [14] gives a necessary and sufficient condition for a prefix language to be regular. Languages whose complement is a prefix language, called "coprefix languages", have also been studied; see Berstel [4] for a survey of results on infinite words whose coprefix language is context-free.…”
Section: Related Workmentioning
confidence: 99%
“…Démonstration ; L'équivalence entre (i), (ii) et (iii) a été établie dans [5]. D'autre part, il est clair que (ii) implique (iv) et (v).…”
Section: Préliminairesunclassified
“…En fait, dès que ^£ est clos par intersection avec les langages rationnels et par homomorphisme, cette propriété est équivalente à : tout langage de S£ défini sur un alphabet d'une seule lettre est rationnel (cf. [5] Nous allons considérer, dans ce papier, une propriété un peu plus faible en nous restreignant aux langages qui ont la propriété de préfixe et qui vérifient L = Init (L) = { x/3 y, xy e L }. Chacun de ces langages est l'ensemble des facteurs gauches d'un mot infini (cf.…”
Section: Introductionunclassified